ASSORTATIVE MATING IN POISON-DART FROGS BASED ON AN ECOLOGICALLY IMPORTANT TRAIT - Reynolds, R. Graham; Fitzpatrick, Benjamin M (Evolution, 2007)
The origin of new species can be influenced by both deterministic and stochastic factors. Mate choice and natural selection may be important deterministic causes of speciation (as opposed to the essentially stochastic factors of geographic isolation and genetic drift). Theoretical models predict that speciation is more likely when mate choice depends on an ecologically important trait that is subject to divergent natural selection, although many authors have considered such mating/ecology pleiotropy, or “magic-traits” to be unlikely. However, phenotypic signals are important in both mate choice and ecological processes such as avoiding predation. In chemically defended species, it may be that the phenotypic characteristics influencing mate choice are the same signals being used to transmit a warning to potential predators, although few studies have demonstrated this in wild populations. We tested for assortative mating between two color morphs of the Strawberry Poison-Dart Frog, Dendrobates pumilio, a group with striking geographic variation in aposematic color patterns. We found that females significantly prefer individuals of their own morph under two different light treatments, indicating strong assortative mating based on multiple coloration cues that are also important ecological signals. This study provides a rare example of one phenotypic trait affecting both ecological viability and nonrandom mating, indicating that mating/ecology pleiotropy is plausible in wild populations, particularly for organisms that are aposematically colored and visually orienting.